Pruning System and Foliar Application of MgSO4 Alter Yield and Secondary Metabolite Profile of Rosa damascena under Rainfed Acidic Conditions - Pal, Probir K.; Mahajan, Mitali (Frontiers in Plant Science, 2017)
Damask rose (Rosa damascena Mill.) is one of the most high-value essential oil bearing plants in the world. However, the flower yield and quality of essential oil of R damascena are largely influenced by the pruning practices and balanced supply of plant nutrition. The objective of this study was to test the hypothesis whether the pruning system and foliar fertilization of MgSO4 would influence the flower yield, growth and secondary metabolites profile of R. damascena. A field experiment of ten treatment combinations comprising two pruning systems (complete and partial) and five levels of MgSO4 (water spray, MgSO4 @ 5.0g L-1 , 10.0g L-1,15.0g L-1, and 20.0g L-1) was conducted. The experiment was conducted in randomized block design with factorial arrangement. Overall, the flower yield ranged from 503.66 -1114.47 g bush-1, while oil content varied from 0.039- 0.046 % of the fresh flower. Irrespective of foliar spray, partial pruning produced significantly (P≤ 0.05) higher flower yield (893.02 and 503.66 g bush-1) compared with complete pruning system in both the years. Regardless pruning system, the foliar application of MgSO4 @ 15.0g L-1 registered about 26 -38 % higher flower yield compared with water spray control. The major constituents essential oil were citronellol (19.75- 48.88%), E-geraniol (9.63- 29.6), Z-citral (0.07- 5.97%), nonadecane (6.76- 22.32 %), and heneicosane (2.87- 10.21%). The Principal component analysis (PCA) revealed that the major hydrocarbons such as nonadecane, nonadecane, and heptadecane are positively and highly correlated with each others. The results suggest that higher yield and quality of R. damascena can be achieved through partial pruning system in combination with foliar application MgSO4 under rainfed acidic conditions.